First record of Siberian weasel Mustela sibirica Pallas, 1773 (Mammalia: Carnivora: Mustelidae) with photographic evidence in Jajarkot, Nepal - Baral, Badri; Basnet, Dipak Raj; Rai, Jeevan; Singh, Gobinda Bahadur; Kathariya, Ramesh; Dhyar, Dhirendra (Nepalese Journal of Zoology, 2025)
Camera traps placed in Nalgaad Municipality, Kuse Rural Municipality, and Barekot Rural Municipality of Jajarkot District, Karnali Province, Nepal showed a new distributional information for Siberian weasel Mustela sibirica. This finding helps fill gaps in our knowledge about the species' distribution, contributing to a more comprehensive understanding of the species' range.